PRE-SERVICE ENGLISH TEACHERS' PERCEPTIONS ON THE INTEGRATION OF MOBILE ASSISTED LANGUAGE LEARNING (MALL) DURING VIRTUAL TEACHING INTERNSHIP - Iin Widya Lestari; Siti Sa'idah; Ainu Zumrudiana; Mohammad Fatoni (ELite Journal : International Journal of Education, Language, and Literature, 2022)
This research was intended to investigate pre-service English teacher's perception of Mobile Assisted Language Learning (MALL) during virtual teaching internships. The problem comes from changing the learning system from offline to online due to pandemic covid 19. Automatically, it influences the implementation of teaching internships. As a result, preschool teachers who carry out the task must adjust the situation. This research is classified into qualitative research. The research participant was five English pre-service teachers who took teaching internship in several schools. The data was obtained by distributing questionnaires, conducting interviews, and analyzing reflective journals. The result shows that EFL pre-service teachers had positive perceptions of the use of MALL in teaching English. Pre-service English teachers understand and are aware of MALL during virtual teaching internships. While the obstacles faced by the Pre-service teacher came from the unstable connection internet access, operating new features, and controlling the students. In conclusion, English pre-service teachers have a positive perception of dealing with MALL application in virtual teaching internships.